Energy Consumption of Indonesian Red Cross (PMI) Building at Wonosobo Regency - Hermawan Hermawan; Ifan Andriawan; Annisa Nabila Arrizqi (Clean Energy and Smart Technology, 2022)
Energy use in health buildings is inevitable due to building functions that must protect specific equipment or parts. One of the health buildings, namely the Indonesian Red Cross (PMI) building, serves to draw people's blood. The use of artificial ventilation must be used to support the function of the PMI building. The study aimed to determine the use or energy consumption of the Indonesian Red Cross (PMI) building in the Wonosobo Regency. The study used the field measurement method for one day. The data collection method also uses the observation method to describe the space and activities in the building. Data analysis uses graphs and compares the outside and inside of the building. AC specifications are also displayed to know how much energy is used. The results showed that the energy consumption of air conditioning in the Wonosobo PMI building was not too large, considering that only specific spaces were used. The outside area is quite remarkable and supports the AC setting, which is not too strong.